PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY UNTUK MENINGKATKAN HASIL BELAJAR IPS PESERTA DIDIK KELAS IV SD NEGERI 003 BERINGIN TALUK KECAMATAN KUATAN TENGAH KABUPATEN KUATAN SINGINGI - Nopridayanti Nopridayanti (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
This research was motivated by the low social science learning outcomes of students in grade IV SD Negeri 003Beringin Teluk. The purpose of this study is to improve students' social science learning outcomes. The design ofthis study uses classroom action research consisting of two cycles. From the data analysis in the first cycleobtained the percentage of the average value of teacher activity in the first cycle was 75% with good categories,after the second cycle the teacher activity increased to 91% with a very good category. Judging from theactivities of students in the first cycle, a percentage value of 70.8% was obtained in the good category, after thesecond cycle, the percentage value increased to 87.5% in the very good category. For the learning outcomes ofstudents, seen from the basic scores of students who complete as many as 13 or 41.93% who achieve theminimum completeness criteria. After being implemented in the first cycle, the learning outcomes of studentsincreased to 21 students or 67.74% which reached the minimum completeness criteria and in the second cyclethe learning outcomes of students returned to 27 students or 87% who achieved the minimum completenesscriteria set by the school that is equal to 70. Thus it can be concluded that the application of the Two Stay TwoStray (TSTS) cooperative learning model can improve the learning outcomes of social science students of thefourth grade of SD Negeri 003 Beringin Teluk.